A Systematic Literature Review : Determinants of Consumer Behaviour in Purchasing Organic Vegetables - Barki, Khotimatul; Rachmah, Malinda Aptika (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2024)
Healthy lifestyle changes have become a trend in modern society. People prefer to consume organic products including organic vegetables. Changes in people's lifestyles strengthen consumer interest in organic products which influences consumer behavior in consuming organic vegetables. This research aims to 1) determine methods regarding consumer behavior in purchasing organic vegetables, 2) determine consumer behavior in decisions to purchase organic vegetables, and 3) find out the factors that influence consumer behavior in purchasing decisions about organic vegetables. The method in this research uses a Systematic Literature Review Study with PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis). Articles are obtained through publication or perish, which is then filtered according to the research concept. Articles are selected according to the keywords used in the research and explained according to the research problem formulation and documentation is carried out. The research results showed that 1) the most frequently used data analysis technique is logistic regression analysis, 2) consumer behavior in purchasing decisions about organic vegetables is influenced by several determinant factors including cultural factors, social factors, personal factors, and psychological factors, 3) the most important factors. important Influencing consumer behavior in purchasing organic vegetables are personal factors.  Knowing in more detail the factors that influence consumer behavior towards purchasing decisions about organic vegetables, can be used as a reference for designing efficient marketing strategies for the organic vegetable market.